2005
DOI: 10.1074/jbc.m507249200
|View full text |Cite
|
Sign up to set email alerts
|

Domain 5 of High Molecular Weight Kininogen Is Antibacterial

Abstract: Antimicrobial peptides are important effectors of the innate immune system. These peptides belong to a multifunctional group of molecules that apart from their antibacterial activities also interact with mammalian cells and glycosaminoglycans and control chemotaxis, apoptosis, and angiogenesis. Here we demonstrate a novel antimicrobial activity of the heparin-binding and cell-binding domain 5 of high molecular weight kininogen. Antimicrobial epitopes of domain 5 were characterized by analysis of overlapping pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 57 publications
4
103
0
Order By: Relevance
“…2B). These results were similar to the bacterial destruction caused by membrane-acting antimicrobial peptides (12,14,15,22). Correspondingly, studies using the impermeant fluorescent probe FITC demonstrated that only HCIIa caused membrane permeabilization of bacterial cells (Fig.…”
Section: Cleaved Hcii Is Antimicrobialsupporting
confidence: 67%
See 1 more Smart Citation
“…2B). These results were similar to the bacterial destruction caused by membrane-acting antimicrobial peptides (12,14,15,22). Correspondingly, studies using the impermeant fluorescent probe FITC demonstrated that only HCIIa caused membrane permeabilization of bacterial cells (Fig.…”
Section: Cleaved Hcii Is Antimicrobialsupporting
confidence: 67%
“…For instance, although ATIII levels are reduced in almost all conditions associated with disseminated intravascular coagulation, reduced plasma levels of HCII are primarily detected during infection (8)(9)(10)(11). Increasing evidence pointing toward a close link between hemostasis, proteolysis, and host defense (12)(13)(14)(15)(16)(17) raised the hypothesis that HCII could play a role in host defense against infections.…”
mentioning
confidence: 99%
“…Microbicidal Potency and Proteolytic Stability-Focusing on two kininogen-derived peptides, GKHKNKGKKNGKHN-GWK (GKH17) and HKHGHGHGKHKNKGKKN (HKH17) (14), hydrophobic end tags were investigated concerning effects of the chemical nature, length, and position of the tags on bactericidal and cytotoxic properties of these peptides. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because cholesterol should preclude membrane tag insertion (25), selectivity between bacteria and eukaryotic cells could also be expected. In the present investigation, this concept was investigated with a focus on previously identified highly charged AMPs derived from kininogen, interesting from a therapeutic perspective because of their ability to withstand infection-related proteolysis (14), another key defense and resistance mechanism of bacteria against AMPs (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation